Fibroblastic growth factor receptor 1 amplification in osteosarcoma is associated with poor response to neo‐adjuvant chemotherapy. (27th May 2014) - Fernanda Amary, M.; Ye, Hongtao; Berisha, Fitim; Khatri, Bhavisha; Forbes, Georgina; Lehovsky, Katie; Frezza, Anna M.; Behjati, Sam; Tarpey, Patrick; Pillay, Nischalan; Campbell, Peter J.; Tirabosco, Roberto; et al.
Abstract Osteosarcoma, the most common primary bone sarcoma, is a genetically complex disease with no widely accepted biomarker to allow stratification of patients for treatment. After a recent report of one osteosarcoma cell line and one tumor exhibiting fibroblastic growth factor receptor 1 (FGFR1) gene amplification, the aim of this work was to assess the frequency of FGFR1 amplification in a larger cohort of osteosarcoma and to determine if this biomarker could be used for stratification of patients for treatment. About 352 osteosarcoma samples from 288 patients were analyzed for FGFR1 amplification by interphase fluorescence in situ hybridization. FGFR1 amplification was detected in 18.5% of patients whose tumors revealed a poor response to chemotherapy, and no patients whose tumors responded well to therapy harbored this genetic alteration. FGFR1 amplification is present disproportionately in the rarer histological variants of osteosarcoma. This study provides a rationale for inclusion of patients with osteosarcoma in clinical trials using FGFR kinase inhibitors.